2009
DOI: 10.1093/cvr/cvp305
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-induced oxidative stress contributes to mitochondrial and cardiac dysfunction in type II diabetes

Abstract: This study demonstrates that NF-kappaB blockade with PDTC mitigates oxidative stress and improves mitochondrial structural integrity directly, through down-regulation of increased oxygen-free radicals, thereby increasing ATP synthesis and thus restoring cardiac function in type II diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 39 publications
(57 reference statements)
3
133
0
1
Order By: Relevance
“…It is known that NF-B activation is a key event for the initiation of cardiovascular pathogenesis in diabetes as a result of increased oxidative stress (56,57). We found that the protein levels of the NF-B1/p50 and p65 subunits were augmented in diabetic vessels and in HG-cultured human coronary SMCs.…”
Section: Discussionmentioning
confidence: 62%
“…It is known that NF-B activation is a key event for the initiation of cardiovascular pathogenesis in diabetes as a result of increased oxidative stress (56,57). We found that the protein levels of the NF-B1/p50 and p65 subunits were augmented in diabetic vessels and in HG-cultured human coronary SMCs.…”
Section: Discussionmentioning
confidence: 62%
“…These results indicated that mitochondrial energetics were impaired in the heart of db/db mice. Mariappan and coworkers discovered that nuclear factor kappa-B (NF-κB) induced oxidative stress and contributed to mitochondrial and cardiac dysfunction in db/db mice (Mariappan et al, 2009). Mitochondrial abnormality was also observed in T1DM Akita mouse hearts (Bugger et al, 2008).…”
Section: Heartmentioning
confidence: 99%
“…For example SF inhibits NF-κB transcription in many cancer models (Srivastava & Singh, 2004;Xu C, 2005). Activation of NF-κB, an upstream regulator of many inflammatory cytokines, has also been well linked to insulin resistance and diabetes (Mariappan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%